2015
DOI: 10.1155/2015/870398
|View full text |Cite|
|
Sign up to set email alerts
|

Acupuncture for Spasticity after Stroke: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: The aim of this systematic review was to determine how effective acupuncture or electroacupuncture (acupuncture with electrical stimulation) is in treating poststroke patients with spasticity. We searched publications in Medline, EMBASE, and the Cochrane Library in English, 19 accredited journals in Korean, and the China Integrated Knowledge Resources Database in Chinese through to July 30, 2013. We included randomized controlled trials (RCTs) with no language restrictions that compared the effects of acupunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 25 publications
(49 reference statements)
0
48
0
4
Order By: Relevance
“…Our trial focused on the pain caused by spasticity and showed that acupuncture is effective at reducing the severity of limb pain. Two recent systematic reviews also concluded that acupuncture is an effective treatment modality for poststroke shoulder pain [17] and spasticity [18]. The obvious between-group difference in posttest VAS scales might indirectly show that acupuncture results in a reduction in the degree of pain caused by spasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Our trial focused on the pain caused by spasticity and showed that acupuncture is effective at reducing the severity of limb pain. Two recent systematic reviews also concluded that acupuncture is an effective treatment modality for poststroke shoulder pain [17] and spasticity [18]. The obvious between-group difference in posttest VAS scales might indirectly show that acupuncture results in a reduction in the degree of pain caused by spasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Тем не менее один из последних метаанализов, выполненный корейскими исследователя-ми, показывает, что иглорефлексотерапия способна уменьшить спастичность и поэтому имеет основание для применения в комплексной терапии пациентов [17].…”
Section: реабилитация больных инсультом направлена на предупреждение unclassified
“…While the underlying mechanisms of acupuncture have not been completely elucidated, and may involve a significant placebo component, there is some evidence that it could help relieve 2 common ALS symptoms: pain (167170) and spasticity (171). …”
Section: Types Of Cam That Pals Commonly Ask Aboutmentioning
confidence: 99%